O kobietach w drukarstwie i typografii. Przyczynek - Seroka, Katarzyna (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Through the ages, men have historically filled the roles associated with the world of bookmaking; however, women have also had valuable roles. While the role of women has not always been the physical creation of books, they have been associated with both the authors and readers of books. The aim of this article is to integrate information about the role of women in printing and typography throughout history.